Numerical Study on Death of Squamous Cell Carcinoma Based on Various Shapes of Gold Nanoparticles Using Photothermal Therapy - Kim, Donghyuk; Kim, Hyunjung (Sensors, 2022)
Due to increased exposure to ultraviolet radiation caused by increased outdoor activities, the incidence of skin cancer is increasing. Incision is the most typical method for treating skin cancer, and various treatments that can minimize the risks of incision surgery are being investigated. Among them, photothermal therapy is garnering attention because it does not cause bleeding and affords rapid recovery. In photothermal therapy, tumor death is induced via temperature increase. In this study, a numerical study based on heat transfer theory was conducted to investigate the death of squamous cell carcinoma located in the skin layer based on various shapes of gold nanoparticles (AuNPs) used in photothermal therapy. The quantitative correlation between the conditions of various AuNPs and the laser intensity that yields the optimal photothermal treatment effect was derived using the effective apoptosis ratio. It was confirmed that optimal conditions exist for maximizing apoptosis within a tumor tissue and minimizing the thermal damage to surrounding normal tissues when using AuNPs under various conditions. Furthermore, it is envisioned that research result will be utilized as a standard for photothermal treatment in the future.
Keywords: Bleedings; Condition; Continuous-wave lasers; Hyperthermia; Outdoor activities; Photo-thermal; Photothermal therapy; Skin cancers; Squamous cell carcinoma; Thermal damage; Carcinoma, Squamous Cell; Cell Line, Tumor; Gold; Humans; Metal Nanoparticles; Photothermal Therapy; Ultraviolet Rays; Apoptosis; Continuous wave laser; Gold nanoparticles; Heat transfer; Hyperthermia; Numerical analysis; Photothermal therapy; Squamous cell carcinoma; Thermal damage